Raja mauritaniensis: a replacement name for Raja africana Capapé, 1977 (Rajiformes: Rajidae), a junior homonym of Raja africana Bloch & Schneider, 1801 (Myliobatiformes: Dasyatidae) - White, William T.; Fricke, Ronald (Zootaxa, 2021)
Raja africana Capapé, 1977 is a primary junior synonym of Raja africana Bloch & Schneider, 1801 and therefore permanently invalid (International Code of Zoological Nomenclature, article 57.2) and must be replaced. Raja africana Bloch & Schneider, 1801 was first described by Bloch & Schneider (1801: 367), based on a specimen from Guinea, West Africa (eastern Atlantic Ocean). The unique holotype is extant in the Zoologisches Museum of the Humboldt University, Berlin (ZMB 7837, a partial dry skin). The species was treated as valid as Urogymnus africanus (Bloch & Schneider 1801) by Compagno & Roberts (1984: 285), but later synonymized with Urogymnus asperrimus (Bloch & Schneider 1801) in the subfamily Urogymninae of the family Dasyatidae (Myliobatiformes) by Compagno (1986: 141), Capapé & Desoutter (1990: 63) and Séret (2016: 1418). It is widespread in the eastern Atlantic, Red Sea and Indo–West Pacific.